ANALISA DESAIN BERDASARKAN TEORI âTHE ESSENTIAL OF DESIGNâ KENDALL PADA SISTEM INFORMASI PERPUSTAKAAN DIGITAL STMIK PPKIA PRADNYA PARAMITA MALANG - Husni, Mochamad; Ihsan, SaÃ¢Â€Â™atul (DINAMIKA DOTCOM, 2012)
Design user interface and data entry procedure STMIK Digital Library Information Systems PPKIA Pradnya Paramita Malang is still not meet the rule of making a good design so that the user interface and data entry procedure can not execute their respective functions resulting digital library is not able to function as sources of information and the science as well as journals or publications of scientific articles in digital format. The theory of